Formation Stages Of Scientific And Technical Texts Translation - Gavrilenko, Nataliya Nikolayevna (Advances in Social Sciences Research Journal, 2015)
The main formation stages of scientific and technical texts translation in France and Russia have been considered in the article. Historiographers find the first references about a written translation of scientific texts in Ancient Greece and Rome. A new cycle of European translation tradition acting in two directions – South-Eastern Europe and Central Europe starts with disintegration of the Roman Empire into Eastern (Byzantine) and Western (Rome). The Arab School of Wisdom in Baghdad and the School of Translators in Toledo greatly influenced the development of those traditions.